Fabrication & Characterization of Chitosan Coated Biologically Synthesized TiO2 Nanoparticles against PDR E. coli of Veterinary Origin - Naheed Zafar; Bushra Uzair; Muhammad Bilal Khan Niazi; Shamaila Sajjad; Ghufrana Samin; Muhammad Javed Arshed; Sikander Rafiq (Advances in Polymer Technology)
Treatment of pandrug resistant (PDR) Escherichia coli strain is the leading causative agent of bovine mastitis worldwide. Hence, becoming a potential threat to veterinary and public health. Therefore, to control the infection new nontoxic, biocompatible antimicrobial formulation with enhanced antibacterial activity is massively required. Current study was planned to synthesize chitosan coated titanium dioxide nanoparticles (CS-NPs coated TiO2). Coating was being done by chitosan nanoparticles (CS-NPs) using ionic gelation method. Aqueous solution of Moringa concanensis leaf extract was used to synthesize titanium dioxide nanoparticles (TiO2 NPs). The synthesized nanoformulations were characterized by using XRD, SEM, and FTIR. X-ray diffraction (XRD) analysis indicated the crystalline phase of TiO2 NPs and CS-NPs coated TiO2 NPs. Scanning Electron Microscopy (SEM) confirmed spherical shaped nanoparticles size of chitosan NPs ranging from 19–25 nm and TiO2 NPs 35–50 nm. Thesize of CS-NPs coated TiO2 NPs was in the range of 65–75 nm. The UV-Vis Spectra and band gap values illustrated the red shift in CS-NPs coated TiO2 NPs. Fourier transform infrared (FTIR) spectroscopy confirmed the linkages between TiO2 NPs and chitosan biopolymer, Zeta potential confirmed the stability of CS-NPs coated TiO2 NPs by showing 95 mV peak value. In-vitro antibacterial activity of CS-NPs coated TiO2 NPs and Uncoated TiO2 NPs was evaluated by disc diffusion method against PDR strain of E. coli isolated from mastitic milk samples. The antibacterial activity of all the synthesized nanoformulations were noted and highest antibacterial activity was shown by CS-NPs coated TiO2-NPs against pandrug resistant (PDR) E. coli strain with the prominent zone of inhibition of 23 mm. Morphological changes of E. coli cells after the treatment with MIC concentration (0.78 μg/ml) of CS-NPs coated TiO2 NPs were studied by transmission electron microscopy TEM showedrigorous morphological defectand has distorted the general appearance of the E. coli cells. Cytotoxicity (HepG2 cell line) and hemolytic (human blood) studies confirmed nontoxic/biocompatible nature of CS-NPs coated biologically synthesized TiO2 NPs. The results suggested that biologically synthesized and surface modified TiO2 NPs by mucoadhesive polysaccharides (e.g. chitosan) coating would be an effective and non-toxic alternative therapeutic agent to be used in livestock industry to control drug resistant veterinary pathogens.